2022
DOI: 10.3389/fpain.2022.861037
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness and Safety of Medical Cannabis for Treating Cancer Related Symptoms in Oncology Patients

Abstract: The use of medical cannabis (MC) to treat cancer-related symptoms is rising. However, there is a lack of long-term trials to assess the benefits and safety of MC treatment in this population. In this work, we followed up prospectively and longitudinally on the effectiveness and safety of MC treatment. Oncology patients reported on multiple symptoms before and after MC treatment initiation at one-, three-, and 6-month follow-ups. Oncologists reported on the patients' disease characteristics. Intention-to-treat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 68 publications
0
7
0
1
Order By: Relevance
“… 1 Following 2016 legislation permitting limited access to cannabis for research and medicinal purposes in Australia, 2 interest in the potential benefits of medicinal cannabis (MC) as an intervention for relief from symptom burden associated with cancer and advanced cancer has increased substantially. 3 , 4 , 5 Several clinical trials have subsequently been initiated. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 Data from trials, especially randomized controlled trials, however, can be ‘difficult to transfer to real‐life experiences’.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Following 2016 legislation permitting limited access to cannabis for research and medicinal purposes in Australia, 2 interest in the potential benefits of medicinal cannabis (MC) as an intervention for relief from symptom burden associated with cancer and advanced cancer has increased substantially. 3 , 4 , 5 Several clinical trials have subsequently been initiated. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 Data from trials, especially randomized controlled trials, however, can be ‘difficult to transfer to real‐life experiences’.…”
Section: Introductionmentioning
confidence: 99%
“…A prospective study among patients with non-cancer pain showed a reasonable safety profile when cannabis was used for a period of one year [ 157 ]. In addition, in the limitedly available clinical studies with patients with cancer, cannabis products generally seem to be tolerated well [ 89 , 158 ]. In a phase I randomised, double-blind, placebo-controlled trial in healthy volunteers, a single dose of up to 6000 mg and multiple doses of 1500 mg twice daily were well-tolerated.…”
Section: Clinical Aspects Of Cannabis Productsmentioning
confidence: 99%
“…Two key phytocannabinoid compounds of medicinal interest found in Cannabis plants include Δ 9 ‐tetrahydrocannabinol (THC) and cannabidiol (CBD), both of which are used to prevent and alleviate a variety of ailments 1 . Pain relief is the most commonly cited reason for medical use of Cannabis 2–5 . Considerable evidence also suggests that cannabinoids exert anticancer effects at multiple levels of tumour progression, 6,7 although Xiong et al 8 .…”
Section: Protecting An Expanding Industrymentioning
confidence: 99%
“…1 Pain relief is the most commonly cited reason for medical use of Cannabis. [2][3][4][5] Considerable evidence also suggests that cannabinoids exert anticancer effects at multiple levels of tumour progression, 6,7 although Xiong et al 8 recently revealed a mechanism suggesting that Cannabis and cannabinoids should be avoided during immunotherapy. There also is a growing body of evidence supporting Cannabis and cannabinoids for treating patients suffering from drug addiction, 9 multiple sclerosis, 10 anorexia nervosa, 11 epilepsy 12 and Tourette syndrome.…”
mentioning
confidence: 99%